Active mass damper control method based on model predictive control using a mode response - Naoto YOSHIDA; Yuta TOMIYOSHI; Akira FUKUKITA; Masaki TAKAHASHI (Mechanical Engineering Journal, 2025)
In this study, we proposed a control method for an active mass damper (AMD) based on model predictive control (MPC) using mode response in super high-rise or mid-to-high-rise buildings. MPC derives the optimal control input within defined constraints, such as the stroke, speed, and thrust of the AMD device, by predicting the future behavior of the controlled object using a mathematical model for each control cycle. When MPC is applied to control building vibrations, first-order modes with large responses dominate as control targets because building responses, such as displacement and velocity, are directly fed back to the control system. However, in super- and mid-to-high-rise buildings, the acceleration response increases owing to the effects of higher-order modes during earthquakes. In such cases, controlling higher-order modes is challenging. The proposed AMD control method controls multiple modes, including higher-order modes, while considering constraints such as the stroke and thrust of the AMD by estimating the modal response using a linear Kalman filter based on the observed building response observed during earthquakes and using the modal response for model predictive control. We verified the effectiveness of the proposed method in reducing the response to seismic disturbance through numerical analysis and shaking table tests using a six-story shear model.